Sarcosine Up-Regulates Expression of Genes Involved in Cell Cycle Progression of Metastatic Models of Prostate Cancer - Heger, Zbynek; Merlos Rodrigo, Miguel Angel; Michalek, Petr; Polanska, Hana; Masarik, Michal; Vit, Vitezslav; Plevova, Mariana; Pacik, Dalibor; Eckschlager, Tomas; Stiborova, Marie; Adam, Vojtech (PloS one, 2016)
The effects of sarcosine on the processes driving prostate cancer (PCa) development remain still unclear. Herein, we show that a supplementation of metastatic PCa cells (androgen independent PC-3 and androgen dependent LNCaP) with sarcosine stimulates cells proliferation in vitro. Similar stimulatory effects were observed also in PCa murine xenografts, in which sarcosine treatment induced a tumor growth and significantly reduced weight of treated mice (p < 0.05). Determination of sarcosine metabolism-related amino acids and enzymes within tumor mass revealed significantly increased glycine, serine and sarcosine concentrations after treatment accompanied with the increased amount of sarcosine dehydrogenase. In both tumor types, dimethylglycine and glycine-N-methyltransferase were affected slightly, only. To identify the effects of sarcosine treatment on the expression of genes involved in any aspect of cancer development, we further investigated expression profiles of excised tumors using cDNA electrochemical microarray followed by validation using the semi-quantitative PCR. We found 25 differentially expressed genes in PC-3, 32 in LNCaP tumors and 18 overlapping genes. Bioinformatical processing revealed strong sarcosine-related induction of genes involved particularly in a cell cycle progression. Our exploratory study demonstrates that sarcosine stimulates PCa metastatic cells irrespectively of androgen dependence. Overall, the obtained data provides valuable information towards understanding the role of sarcosine in PCa progression and adds another piece of puzzle into a picture of sarcosine oncometabolic potential.
Keywords: Cell Cycle; nádorové buněčné linie; Up-Regulation; Mice, Inbred BALB C; Sarcosine; Sarcosine Dehydrogenase; glycin-N-methyltransferasa; Glycine N-Methyltransferase; upregulace; Neoplasm Transplantation; regulace genové exprese u nádorů; transkriptom; polymerázová řetězová reakce; Polymerase Chain Reaction; sarkosin; sarkosindehydrogenasa; mužské pohlaví; nádory prostaty; Mice; Cell Line, Tumor; Genes, Neoplasm; Transcriptome; buněčný cyklus; Mice, Nude; geny nádorové; Prostatic Neoplasms; zvířata; Humans; Gene Expression Regulation, Neoplastic; transplantace nádorů; myši nahé; myši inbrední BALB C; myši; lidé; Male; Animals